La lectura inferencial de textos en inglés en estudiantes de habla española - Calle Álvarez, Gerzon Yair; Achicanoy Chaparro, Patricia del Carmen (Colombian Applied Linguistics Journal, 2024)
This article aims to understand the inferential reading strategies employed by Spanish-speaking eleventh-grade students when reading English texts. The methodology used adopts a qualitative approach and its design is framed within a collective case. The instruments employed in this study were a reading test and a semi-structured interview. The study involved the participation of five eleventh-grade students from a public educational institution in the city of Medellin, Colombia. These students engaged in four readings encompassing descriptive, narrative, expository, and argumentative texts. The results showed that the most frequently applied inference strategies were retroactive, while the least frequently applied were logical and projective. The study concludes that enhancing inferential reading in English among Spanishspeaking students necessitates the development of pre-reading strategies that contribute to both situational and linguistic understanding of the text, as well as promoting re-reading practices among students.